The Implementation of Phonics Method to Improve Reading Skills in Language Learning - Situmorang, Naila Izzatul Fikriyah; Anggraini, Nadia; Qonitah, Mutiara; Az- Zahra, Zafira; Erli, Ika Sucinta; Pebriana, Putri Hana (The Future of Education Journal, 2025)
This study's objective is to provide a description of one approach to enhancing reading abilities, namely through the utilization of the phonics technique. In addition, the purpose of this research is to investigate the efficacy of the phonics approach in improving reading abilities in the context of language acquisition. Phonics is a teaching strategy that places an emphasis on the connection between individual letters and the sounds they represent. This method assists pupils in better comprehending the structures of words and how they should be spoken. All of the participants in this study are elementary school pupils, and the research is conducted using a quantitative methodology and an experimental design. This strategy was implemented, and the findings of the study demonstrate that students' reading skills significantly improved after it was implemented. This development was notably noticeable in the areas of letter recognition, pronunciation, and word comprehension. Data collection tools in this study involved searching journals online through platforms like Google Scholar. This study aims to analyze how the phonics method can enhance students' reading skills in the context of Indonesian language learning. This study investigates the efficacy of the phonics approach in increasing students' reading abilities, including decoding skills and reading comprehension, by conducting a literature evaluation of fifteen research publications that have been published over the past five years. The findings of the review suggest that the phonics technique is an excellent means of enhancing the reading abilities of kids, and this holds true for students who have normal reading abilities as well as students who are trying to improve their reading abilities. This makes the phonics method a relevant approach for implementation in Indonesian language learning.